Determinant of Firm Value and the Role of Firm Size as a Moderating Variable: Empirical Evidence from Top 100 Listed Companies in Indonesia - Eka, Yuliana Yuspita; Azazi, Anwar; Syahbandi; Wendy; Mustika, Uray Ndaru (MultiTech Publisher, 2025)
Firm value reflects investors’ confidence in a company’s management capabilities, ultimately affecting their financial returns. Assessing a firm's value is crucial for investment decisions as it shapes investor perceptions. This research aims to examine the influence of profitability, tax planning, and leverage on firm value in Indonesian companies listed on the Kompas 100 index, with firm size as a moderating variable. The samples were selected using purposive sampling, yielding 222 observations from 37 companies. The panel data were analyzed using moderated regression analysis with EViews 13. The findings reveal that whereas leverage has no appreciable beneficial effect on firm value, profitability and tax planning do. Furthermore, firm size significantly moderates these relationships, enhancing the positive effects of profitability and tax planning, and mitigating the negative impact of leverage on firm value. This research implies that in corporate management should prioritize profitability through operational efficiency and sustainable growth strategies, and utilize legal and efficient tax planning to enhance firm value